Performance of seal vibrissa-inspired bionic surface in suppressing aerodynamic forces and vortex shedding around a circular cylinder. (15th September 2022) - Chen, Wen-Li; Min, Xiang-Wei; Guo, Yan-Jiao
Abstract: In this study, circular cylinders with bionic surfaces were developed to control the flow fields around cylindrical structures such as stay cables of bridges. The bionic cylinder geometries were characterized by slanted elliptical governing sections and wave surfaces. Wind tunnel experiments were conducted to identify the surface pressure distributions, aerodynamic forces, and flow field characteristics of bionic circular cylinders at a Reynolds number ( Re ) of 3.8 × 10 4 . The results show that the aerodynamic forces of the bionic cylinders are sensitive to the wind attack angle ( γ ) and wave surface wavelength. The control effects were excellent at γ  = 0°, 90°, and 180°, whereas they vanished at γ  = 45° and 135° compared with a baseline circular cylinder. When the wavelength range of the bionic cylinder is 4 D –5 D, the maximum reductions in the mean drag and fluctuating lift were 27% and 93%, respectively. The vortex formation region was elongated, and the alternative vortex shedding process was suppressed. Proper orthogonal decomposition was performed to determine the coherent structure of the wake field and the boundary vorticity flux analysis demonstrates the difference in the strength of the wake vortex from the viewpoint of boundary vorticity diffusion between the fluid and wall. Spatial–temporal correlation analysis of the velocity profiles behind different cross-sections shows that the wave surface troughs contribute significantly to disrupting the flow consistency in the spanwise direction. Highlights: A bionic cylinder characterized by wave surface and slanted elliptical governing sections was investigated. The bionic surface could reduce the mean drag and fluctuating lift of the cylinder. The flow structures, POD modes, and boundary vorticity flux were analyzed to explore the control mechanism. The control method could decrease the spanwise correlation of the wake velocity and enhance the characteristics of the three-dimensional flow.